Combination Therapy Strategies Against Multiple-Resistant Streptococcus Suis - Yu, Yang; Fang, Jin-Tao; Zheng, Mei; Zhang, Qing; Walsh, Timothy R.; Liao, Xiao-Ping; Sun, Jian; Liu, Ya-Hong (Frontiers in Pharmacology, 2018)
Streptococcus suis is a major swine pathogen, an emerging zoonotic agent responsible for meningitis, endocarditis and septicaemia followed by deafness in humans. The development of antimicrobial resistance in S. suis increases the risk for therapeutic failure in both animals and humans. In this study, we report the synergism of combination therapy against multi-resistant S. suis isolates from swine. Twelve antibiotic profiles were determined against 11 S. suis strains. To investigate their synergistic/antagonistic activity, checkerboard assay was performed for all the possible combinations. In-vitro killing curves and in-vivo treatment trials were used to confirm the synergistic activity of special combinations against S. suis dominant clones. In this study, 11 S. suis isolates were highly resistant to erythromycin, clindamycin, trimethoprim/sulfamethoxazole and tetracycline with ratios of 80% to 100%, and the resistance percentages to enrofloxacin, florfenicol and spectinomycin were approximately 50%. The checkerboard data identified two combination regimens, ampicillin plus apramycin and tiamulin plus spectinomycin which gave the greatest level of synergism against the S. suis strains. In-vitro kill-curves show a bacterial reduction of over 3-logCFU with the use of combination treatments, whilst the application of mono-therapies achieve less than a 2-logCFU cell killing. In-vivo models confirm that administration of these two combinations significantly reduced the number of bacterial cells after 24 hours of treatment. In conclusions, the combinations of ampicillin plus apramycin and tiamulin plus spectinomycin showed the greatest synergism and may be potential strategies for treatment of multi-resistant S. suis in animal.